PENGEMBANGAN ENSIKLOPEDIA PERALATAN LABORATORIUM KIMIA SEBAGAI SUMBER BELAJAR SISWA SMA NEGERI 10 PONTIANAK - Rizki Sindi Susanti; Dedeh Kurniasih; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2019)
This research was motivated by students’ low knowledge related to the name, function, and the way of using Chemical laboratory tools during the experiment. This research aimed to create the Encyclopedia of Chemical Laboratory Tools which valid and practical Learning Source for students in SMA Negeri 10 Pontianak. The development model used in this research was adapted and modified from the steps of ADDIE development model consist of an analysis, design, development, implementation, and evaluation. The data collection technique used in this research was an indirect communication technique. The validator of this encyclopedia used a questionnaire with likert scale for the response as the instrument. The analysis result showed that the Encyclopedia of Chemical Laboratory Tools was valid with 1,00 practical values that was reflected from students’ and teachers’ responses with an average value around 85,5% with a very high criteria. Therefore, it can be concluded that the Encyclopedia of Chemical Laboratory Tools from ADDIE development model has a very good quality. Therefore, it can be properly used as a learning source for students in SMA Negeri 10 Pontianak.